Ballistic design and testing of a composite armour reinforced by CNTs suitable for armoured vehicles - Tsirogiannis, Evangelos Ch. (2024)
This paper is investigating the use of composite armour reinforced by nanomaterials, for the protection of light armoured (LAV) and medium armoured military vehicles (MAV), and the interaction between the composite materials and high-performance ballistic projectiles. Four armour materials, consisted of front hybrid fibre reinforced polymer cover layer, ceramic strike-face, fibre reinforced polymer intermediate layer and the metal matrix composite reinforced backplate, were manufactured and assembled by adhesive technology. The proposed laminated protection system is suitable for armoured ground vehicles; however, it could be used as armour on ground, air and naval platforms. The design of the protection system, including material selection and thickness, was elaborated depending on the performance requirements of Level 4 ＋ STANAG 4569 military standard (projectile 14.5 mm × 114 mm API B32) and especially on a design philosophy which is analysed with the specifications. The backplate of this new composite is a hybrid material of Metal Matrix Composite (MMC) reinforced with carbon nanotubes (CNTs), manufactured with the use of powder metallurgy technique. The composite backplate material was morphologically, mechanically and chemically analysed. Results show that all plates are presenting high mechanical properties and ballistic characteristics, compared to commonly used armour plates. Real military ballistic tests according to AEP - STANAG 4569 were carried out for the total composite armour systems. After the ballistic tests, AA2024-CNT3 showed the best protection results, compared with the other plates (AA2024-CNT1 and AA2024-CNT2), with the projectile being unable to fully penetrate the composite plate.